TRANSPARANSI PEMERINTAH DESA TERHADAP PENGELOLAAN DANA DESA TALAWE KECAMATAN WATANG SIDENRENG KABUPATEN SIDENRENG RAPPANG - Muhammad Ridwan (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2020)
Absract This study aims to determine the transparency of the village government in Talawe Village, Watang Sidenreng District, Sidenreng Rappang Regency, to find out the management of village funds in Talawe Village, Watang Sidenreng District, Sidenreng Rappang District, and to determine village government transparency in village fund management in Talawe Village, Watang Sidenreng District Sidenreng Rappang. The population in this study was 345 heads of households in which the sampling used was Non-Probability Sampling, with a Purposive sampling technique with a total sample of 35 people. This study used a Quantitative Descriptive Method. Data collection techniques used through observation, questionnaires (questionnaires), library studies, and interviews. The data analysis technique used is frequency tabulation analysis and simple regression analysis with the help of the SPSS version 16.0 program. The results of this study indicate that the Transparency of the Village Government in Talawe Village, Watang Sidenreng District, Sidenreng Rappang Regency has an average percentage of 58% categorized as